Application of skin care bundles for pediatric patients with type 1 diabetes mellitus (集束化干预策略在1型糖尿病患儿皮肤管理中的应用) - WANG Qiao (王巧); YI Junli (易君丽) (中西医结合护理)
Objective To improve the treatment compliance of pediatric patients with type 1 diabetes mellitus and reduce the risk of skin-related complications by using a skin care bundles. Methods According to the sequence of hospital admission, 36 pediatric patients with type 1 diabetes mellitus were recruited as the control group, and another 36 pediatric patients were recruited as the study group. The control group received routine skin care during hospitalization, and the study group received a skin care bundles on the basis of routine skin management. The treatment compliance and incidence of skin problems related to insulin injection and fingerstick blood glucose monitoring were compared between two groups. Results The treatment compliance rate in the study group was higher than that in the control group(P＜0. 01). The incidences of skin problems skin problems related to insulin injection and fingerstick blood glucose monitoring in the study group were lower than those in the control group (P＜0. 01). Conclusion The skin care bundle is effective to improve the treatment compliance of pediatric patients with type 1 diabetes mellitus and reduce the risk of skin problems related to insulin injection. (目的 通过采用集束化干预策略提高1型糖尿病患儿皮肤管理的依从性, 降低皮肤问题的发生风险。方法 选择2019年1月-12月住院的36名1型糖尿病患儿作为对照组, 选取2020年1月-12月住院的36名1型糖尿病患儿作为试验组。对照组接受常规皮肤管理, 试验组在常规皮肤管理的基础上, 采用集束化管理策略。评估2组患儿皮肤管理的依从性, 记录胰岛素注射导致皮肤问题和指尖血糖监测相关皮肤问题的发生情况。结果 试验组皮肤管理的依从率高于对照组, 胰岛素注射导致皮肤问题和指尖血糖监测相关皮肤问题的发生率均低于对照组, 差异有统计学意义(P＜0. 01)。结论 集束化管理可以提高糖尿病患儿皮肤管理的依从率, 降低并发症的发生风险, 从而有利于提高照护者居家照护的质量。)